Work-related musculoskeletal disorders amongst undergraduate nursing students at the University of Johannesburg - Malany Moodley; Fatima Ismail; Armand Kriel (AOSIS, 2020)
Background:Work-related musculoskeletal disorders (WRMSDs) present as pain or discomfort in the musculoskeletal system that individuals experience from work-related activities. Substantial research evidence exists on qualified nurses with WRMSDs, but there is a distinct lack of research regarding nursing students and their work environment in South Africa. Aim: The primary aim of this study was to establish a baseline prevalence of musculoskeletal disorders (MSDs) amongst undergraduate nursing students. The secondary aim was to identify the role of certain occupational and biopsychosocial factors in the development of MSDs. Setting: The University of Johannesburg, Health Sciences Faculty, Doornfontein Campus, Johannesburg, South Africa. Method: A cross-sectional quantitative study conducted through a questionnaire (from 24 June to 29 July 2019) was initiated amongst the undergraduate nursing students at the University of Johannesburg, South Africa. All 250 undergraduate nursing students were given the opportunity to participate by completing the Nordic Musculoskeletal Questionnaire-Extended (NMQ-E). A total of 125 questionnaires were collected and used in the study. Data analysis consisted of frequencies, descriptives and custom tables. The Chi-square test for association was used to test the associations between variables. Results: The study found an 83% prevalence of MSDs. Musculoskeletal disorders occurred most commonly in the lower back (81.1%), neck (65.9%) and shoulder (63.6%) regions. Factors that showed associations with overall MSDs were female gender (p = 0.002), height (p = 0.009) and studying at home (p = 0.040). Stress and tablet or smartphone use had significant associations with certain body regions. Conclusion: The findings indicate a high prevalence of MSDs in undergraduate nursing students in this sample, substantially higher than in other similar studies in which lower back disorders were most prevalent.